Syndication networks and company survival: Evidence from European venture-capital deals - Dimitris Christopoulos; Stefan Köppl; Monika Köppl-Turyna (EcoAustria - Institute for Economic Research, 2021)
We look at syndication in the venture capital industry. Investments conducted by syndicates are believed to have better chances of being successful, measured by the survival probability of portfolio companies or by successful exits. Using a novel and large dataset, covering several countries, our analysis shows that strong network ties of investors are associated with success of portfolio companies in Europe. We also show that there are differences in the association of network centrality with survival between different financing rounds, the former being more important in early-stage investments. Finally, we show a strong association of network ties of investors with sales growth of portfolio companies, before and after the deal.
Keywords: G11; G24; M13; 330; Venture Capital; Networks; Europe; Investment Syndication